Kemampuan Penalaran Matematis Siswa Kelas VIII A SMPN 3 Srengat dengan Gaya Belajar Visual dalam Memecahkan Masalah Matematika pada Materi Bentuk Aljabar - Fitriati Hamidah; Syaiful Hadi (Wacana Akademika: Majalah Ilmiah Kependidikan, 2023)
One of the abilities that students should be masters of is the capacity for mathematical reasoning. The ability of good mathematical reasoning will really help them in resolving common mathematical problems. Another aspect that affects student’s ability to solve problems requiring mathematical reasoning is learning style. The study uses  a method that is qualitative with the type of case study. The purpose of this study is to describe the ability of mathematical reasoning of Class VIII A at Srengat 3 Junior High School to a visual learning style in solving mathematical problems on the material algebraic form. The results showed that students with visual learning styles are able to meet 4 indicators of the ability of mathematical reasoning, which is sense-making, conjecturing, convincing, and generalising.